Survey and rapid detection of Klebsiella pneumoniae in clinical samples targeting the rcsA gene in Beijing, China - Dong, Derong; Liu, Wei; Li, Huan; Wang, Yufei; Li, Xinran; Zou, Dayang; Yang, Zhan; Huang, Simo; Zhou, Dongsheng; Huang, Liuyu; Yuan, Jing (Frontiers in Microbiology, 2015)
Klebsiella pneumoniae is a wide-spread nosocomial pathogen. A rapid and sensitive molecular method for the detection of K. pneumoniae in clinical samples is needed to guide therapeutic treatment. In this study, we first described a loop-mediated isothermal amplification (LAMP) method for the rapid detection of capsular polysaccharide synthesis regulating gene rcsA from K. pneumoniae in clinical samples by using two methods including real-time turbidity monitoring and fluorescence detection to assess the reaction. Then dissemination of K. pneumoniae strains was investigated from ICU patients in three top hospitals in Beijing, China. The results showed that the detection limit of the LAMP method was 0.115 pg/µl DNA within 60 min under isothermal conditions (61°C), a 100-fold increase in sensitivity compared with conventional PCR. All 30 non- K. pneumoniae strains tested were negative for LAMP detection, indicating the high specificity of the LAMP reaction. To evaluate the application of the LAMP assay to clinical diagnosis, of 110 clinical sputum samples collected from ICU patients with clinically suspected multi-resistant infections in China, a total of 32 K. pneumoniae isolates were identified for LAMP-based surveillance of rcsA. All isolates belonged to nine different K. pneumoniae multilocus sequence typing (MLST) groups. Strikingly, of the 32 K. pneumoniae strains, 18 contained the Klebsiella pneumoniae Carbapenemase (KPC)-encoding gene blaKPC-2 and had high resistance to β-lactam antibiotics. Moreover, K. pneumoniae WJ-64 was discovered to contain blaKPC-2 and blaNDM-1 genes simultaneously in the isolate. Our data showed the high prevalence of blaKPC-2 among K. pneumoniae and co-occurrence of many resistant genes in the clinical strains signal a rapid and continuing evolution of K. pneumoniae. In conclusion, we have developed a rapid and sensitive visual K. pneumoniae detection LAMP assay, which could be a useful tool for clinical screening, on-site diagnosis.